Aspirin Use and the Incidence of Hepatocellular Carcinoma in Patients With Hepatitis B Virus or Hepatitis C Virus Infection: A Meta-Analysis of Cohort Studies - Li, Xiaofei; Wu, Shuang; Yu, Yuexiao (Frontiers in Medicine, 2021)
Background: The association between aspirin use and the incidence of hepatocellular carcinoma (HCC) in patients with hepatitis B virus (HBV) or hepatitis C (HCV) virus infection remains not fully determined. A meta-analysis was performed to summarize findings of cohort studies. Methods: Relevant cohort studies were retrieved via search of PubMed Cochrane’s Library, and Embase databases. A random-effect model was used to pool the results. Subgroup analyses were performed to evaluate the influence of study characteristics on the association. Results: Seven cohort studies with 120,945 adult patients with HBV or HCV infection were included. Pooled results showed that aspirin use was independently associated with a reduced risk of HCC in these patients (risk ratio [RR]: 0.73, 95% CI: 0.64 to 0.83, p < 0.001; I2 = 86%). Subgroup analyses showed that aspirin use was associated with a reduced HCC risk regardless of the viral type, age, sex, diabetic and cirrhotic status of the patients, as well as the follow-up durations. Moreover, consistent results were obtained in studies with and without adjustment of antiviral treatment and statin use. Pooled results of four studies showed that aspirin use was associated with an increased risk of gastrointestinal bleeding (GIB) in these patients (RR: 1.15, 95% CI: 1.02 to 1.28, p = 0.02; I2 = 0%). Conclusions: Aspirin use was independently associated with a reduced risk of HCC in patients with HBV or HCV infection, while the risk of GIB may be increased. These results should be validated in clinical trials.